Horizontal Mergers and Product Quality - Kurt R. Brekke; Luigi Siciliani; Odd Rune Straume (Center for Economic Studies and ifo Institute (CESifo), 2015)
We study the effects of horizontal mergers when firms compete on quality and price. Two key factors are identified: (i) the magnitude of variable quality costs, and (ii) the relative magnitudes of cross-quality and cross-price effects on demand. The merging firms will increase (reduce) both quality and price if the degree of competition is sufficiently stronger (weaker) on price than on quality. If variable quality costs are sufficiently small, non-merging firms will respond to a merger by either reducing or increasing both price and quality. Welfare implications are not clear-cut and mergers might improve welfare through endogenous fixed-cost savings.
Keywords: L13; L15; L41; 330; horizontal mergers; quality and price competition